Alternative Approaches to Motor Vehicle Tax in Turkey - Citci, S. Haluk; Karakas, Mesut; Erdogan, Ugur (Maliye Bakanligi, 2016)
In this study, motor vehicles tax is examined focusing on the principles of justice, environmental protection and public revenue, and alternative systems based on price range, price percentage and carbon-dioxide emission are developed. The effects of the alternative approaches on carbon-dioxide emission, tax income, and justice are analyzed via demand simulations. Results show that alternative system based on vehicle price range efficiently reduces carbon-dioxide emission however it's not successful in ensuring tax justice. The system based on carbon-dioxide emission requires tax rates to be considerably increased. Fortunately, approach based on price percentage of vehicle yields improvements on carbon-dioxide emission while ensuring tax justice.
Keywords: Motor Vehicles Tax; Tax Justice; CO2 Emission